Kinoscope: An Open-Source Computer Program for Behavioral Pharmacologists - Kokras, Nikolaos; Baltas, Dimitrios; Theocharis, Foivos; Dalla, Christina (Frontiers in Behavioral Neuroscience, 2017)
Behavioral analysis in preclinical neuropsychopharmacology relies on the accurate measurement of animal behavior. Several excellent solutions for computer-assisted behavioral analysis are available for specialized behavioral laboratories wishing to invest significant resources. Herein, we present an open source straightforward software solution aiming at the rapid and easy introduction to an experimental workflow, and at the improvement of training staff members in a better and more reproducible manual scoring of behavioral experiments with the use of visual aids-maps. Currently the program readily supports the Forced Swim Test, Novel Object Recognition test and the Elevated Plus maze test, but with minor modifications can be used for scoring virtually any behavioral test. Additional modules, with predefined templates and scoring parameters, are continuously added. Importantly, the prominent use of visual maps has been shown to improve, in a student-engaging manner, the training and auditing of scoring in behavioral rodent experiments.